2020
DOI: 10.1038/s41698-020-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of pro-inflammatory soluble cytokine receptors early during hepatocellular carcinoma stereotactic radiotherapy with liver toxicity

Abstract: Plasma levels of soluble factors early during hepatocellular carcinoma (HCC) stereotactic body radiotherapy (SBRT) were evaluated in relation to radiation liver injury, tumor response, and risk of early death. No significant differences were found in baseline plasma levels of AFP, CXCL1, and HGF amongst HCC patients with different Child Pugh scores. Higher levels of sTNFRII (P < 0.001), and lower levels of sCD40L (P < 0.001) and CXCL1 (P = 0.01) following one to two fractions of SBRT were noted in patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…A divergent activity of pro-inflammatory cytokines, such as tumor necrosis factor α, was noted between HCC patients of different CTP scores at baseline and early during liver SBRT. 35,36 This variable cytokine profile by liver function was suggested to mediate the differential radiation sensitivity of the liver and the development of liver toxicity, thereby affecting survival. In this cohort, the baseline CTP class was identified as the only predictor of dNLR after SBRT, and the difference in dNLR between CTP groups mainly arises from the post-SBRT change.…”
Section: Discussionmentioning
confidence: 99%
“…A divergent activity of pro-inflammatory cytokines, such as tumor necrosis factor α, was noted between HCC patients of different CTP scores at baseline and early during liver SBRT. 35,36 This variable cytokine profile by liver function was suggested to mediate the differential radiation sensitivity of the liver and the development of liver toxicity, thereby affecting survival. In this cohort, the baseline CTP class was identified as the only predictor of dNLR after SBRT, and the difference in dNLR between CTP groups mainly arises from the post-SBRT change.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that in prostate cancer, cytokine changes during RT had a predictive role in gastrointestinal and genitourinary toxicity. Ng et al [ 25 ] assessed the changes of pro-inflammatory cytokine receptors in patients with hepatocellular carcinoma treated with stereotactic radiotherapy. The patients who developed chronic liver toxicity showed significantly higher levels of sTNFRII, and lower levels of sCD40L and CXCL1 early during stereotactic body radiation therapy (SBRT); in addition, early death after SBRT was significantly related to high levels of sTNFRII and sIL-6R after one to two fractions of SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…The greater likelihood of developing acute grade  2 GI and GU toxicities after SBRT in the IBD cohort may be associated to the underlying processes causing chronic inflammation in IBD patients and an immunomodulatory response from radiotherapy 16,17 . Pre-clinical data suggests that SBRT-induced tumor cell death triggers the release of tumor antigens and inflammatory cytokines 18 , which could increase the risk of developing both GI and GU toxicity. This is supported by the delayed occurrence of urinary symptoms after SBRT and rapid symptomatic response to oral steroids 19 .…”
Section: Discussionmentioning
confidence: 99%